Conjugate heat and mass transfer at heterogeneous burning surface of AP/HTPB/Al composite propellant at 2–10 MPa. (5th June 2023) - Liu, Shuyuan; Han, Luyang; He, Pengxiang; Wang, Limin; Han, Jinchao; Hu, Songqi
Graphical abstract: Heat release rate of AP/HTPB/Al composite propellant at different pressure. Highlights: Detailed mechanism with 42 species and 136 reactions is established for AP/HTPB/Al. Segregated burning rate model is established for heterogeneous burning surface. Contributions of heat convection and radiation are quantitatively evaluated. Increase of pressure and Al content reduces heterogeneity of burning surface. Abstract: Conjugate heat and mass transfer at heterogeneous burning surface has significant effect on combustion characteristics of AP/HTPB/Al composite propellant. In the present study, the conjugate heat and mass transfer characteristics of AP/HTPB/Al composite propellant are studied experimentally and numerically based on formulated combustion model and experimental facilities. With the increase of pressure and Al content, flame temperature increases significantly and leads to stronger heat transfer to the burning surface. With the content of Al varying from 18 wt% to 9 wt%, the total heat transfer coefficient decreases for all the sampled positions of the burning surface with a maximum decrease of 12% at the AP/HTPB interface. It is found that heat convection accounts for more than 97% of the total heat transfer coefficient. However, with pressure increasing from 2 MPa to 10 MPa, the total heat transfer coefficient and the respective contribution of heat convection and radiation vary slightly. Owing to the heterogeneous sandwich-like structure of the propellant, the temperature distribution at the burning surface of propellant is highly non-uniform. Therefore, heat transfer characteristics vary significantly at different positions of the burning surface. The heterogeneity of the burning surface is exacerbated by the non-uniform distribution of heat transfer coefficients at different positions of the burning surface. The burning rate of the propellant varies from 0.5 mm/s to 9.5 mm/s for different positions of the burning surface at 10 MPa. The results of micro-scale flame structure show that the mass transfer of fine Al particles in the combustion of AP/HTPB/Al composite propellant can be basically divided into four stages, i.e., migration, melting, agglomeration and oxidation/combustion. Coral reef-like aggregate structure is formed by some of the fine Al particles before oxidation and combustion. Increasing pressure is conducive to avoiding formation of large Al agglomerates and enhancing mass transfer at the heterogeneous burning surface.